Predicting Recidivism in a High-Risk Sample of Intimate Partner Violent Men Referred for Police Threat Assessment - Pham, Anna T. (Criminal justice and behavior, 2023)
It is unknown whether existing intimate partner violence (IPV) risk assessment tools can predict recidivism within threat assessment samples. We examined the predictive validity for IPV, any violent, and general recidivism of four commonly used IPV risk appraisal tools (Ontario Domestic Assault Risk Assessment [ODARA], Spousal Assault Risk Assessment version 2 [SARA-V2], SARA version 3 [SARA-V3], and Brief Spousal Assault Form for the Evaluation of Risk [B-SAFER]) with 247 men charged with IPV and referred to a threat assessment service. Total scores of the ODARA and SARA-V2—but not SARA-V3 or B-SAFER—significantly predicted IPV recidivism and any violent recidivism. The SARA-V2 Criminal History subscale and the B-SAFER subscale of “Past” events—but no other subscales of the SARA-V2, B-SAFER, or SARA-V3—significantly predicted IPV recidivism. Although effect sizes were smaller than in past research, our results support the use of the ODARA and SARA-V2 with threat assessment IPV populations.